1995
DOI: 10.1093/clinids/20.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Schistosoma haematobium Infection Despite Multiple Courses of Therapy with Praziquantel

Abstract: A 7-year-old boy, who had returned to the United States in June 1991 after a 3-year stay in Malawi, was evaluated in October 1991 because of hematuria. He was excreting Schistosoma haematobium eggs and was treated with praziquantel (PZQ; approximately 40 mg/kg). He may have spit up < or = 30% of this dose, and a concomitant Giardia lamblia infection might have caused malabsorption of PZQ. Because of persistent excretion of viable eggs, he was retreated with PZQ in January and May 1992. Egg excretion was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
1
19
3
Order By: Relevance
“…Of the 89 reviewed documents, 22 (25%) reported on individuals who had developed signs and symptoms of schistosomiasis after returning from a visit to Malawi. These documents comprised 13 case reports and 9 letters to the editor written by non-Malawian authors [25,30,[33][34][35][36][37][38][39][40][46][47][48][49][50][51][52][53][54][55][56][89][90][91]94,95,97,107].…”
Section: Schistosomiasis and Tourism In Malawimentioning
confidence: 99%
“…Of the 89 reviewed documents, 22 (25%) reported on individuals who had developed signs and symptoms of schistosomiasis after returning from a visit to Malawi. These documents comprised 13 case reports and 9 letters to the editor written by non-Malawian authors [25,30,[33][34][35][36][37][38][39][40][46][47][48][49][50][51][52][53][54][55][56][89][90][91]94,95,97,107].…”
Section: Schistosomiasis and Tourism In Malawimentioning
confidence: 99%
“…Although praziquantel is the drug of choice for the treatment of S. haematobium infections (Gentilini et al 1982, McMahon 1983, Pugh & Teesdale 1984, Stephenson et al 1989, McNeeley et al 1990, King et al 1992, King & Mahmoud 1999, King et al 2002, cases of treatment failure have been frequently reported, probably due to a progressive increase in the resistance of the parasite to the drug, as observed by some authors (Groning et al 1985, Herwaldt et al 1995, Hatz et al 1998, Ernould et al 1999, Liang et al 2000. Despite the controversies regarding the rapid emergence of praziquantel resistance, constant surveillance of this progression is important.…”
Section: Discussionmentioning
confidence: 99%
“…These important factors have contributed to the tolerance with and easy application of individualized and mass treatments (Stephenson et al 1989, King et al 1992. Nevertheless, failure of praziquantel treatment of various proportions has been reported (Herwaldt et al 1995, Liang et al 2000. So, it is necessary to be sure about the + Corresponding author.…”
mentioning
confidence: 99%
“…However, the mechanism of action of PZQ is still unidentified although data shown it causes schistosomes to develop tetanic contractions and tegumental vacuoles; affected worms lose their hold on the vein wall, and then washed upstream to the liver and die [6][7][8]. Several PZQ-resistant isolates already have identified [9,10]. There have been several studies to modify PZQ, but have yet to reach clinical trials [11].…”
Section: Introductionmentioning
confidence: 99%